Outbreaks of a new invasive pest, the fall armyworm (Spodoptera frugiperda) in South Sumatra, Indonesia. Issue 1 (November 2021) - Herlinda, S; Sinaga, M E; Ihsan, F; Fawwazi, F; Suwandi, S; Hasbi,; Irsan, C; Suparman,; Muslim, A; Hamidson, H; Arsi,; Umayah, A; et al.
Abstract: Spodoptera frugiperda is polyphagous besides attacking maize, it can attack other plant species from various families. Information about the attack and population of S. frugiperda in various maize production centers in Indonesia is still limited. This study aimed to find out the population and attack of S. frugiperda in South Sumatra. Surveys were carried out from the lowlands to the highlands of South Sumatra, such as Palembang City, Pagar Alam City, Lahat City, Ogan Ilir District, Prabumulih City, Muara Enim District, Banyuasin District. The mean percentage severity of S. frugiperda in South Sumatra reached 34.75%, and its percentage of mean incidence reached 78%. The highest larvae density was found in Pagaralam City with an average of 0.29 larvae/100 plants, while the lowest was found in Muara Enim District (0.08 larvae/100 plants). The population density of larvae began to occur at the age of 3 to 5 weeks, after that the larvae were not found in maize fields. We found that outbreaks of S. frugiperda have occured in the South Sumatra.